2021
DOI: 10.1097/hcr.0000000000000649
|View full text |Cite
|
Sign up to set email alerts
|

Review of Recent Cardiac Rehabilitation Research Related to Enrollment/Adherence, Mental Health, and Other Populations

Abstract: This review overviews three topic areas observed to be highly active in the cardiac rehabilitation (CR) research literature published in 2019 and 2020. Topics summarized were enrollment or adherence in CR programs; mental health, particularly depression, stress, and anxiety of patients participating in CR programs; and patients participating in CR programs with diagnoses other than coronary artery bypass graft, myocardial infarction, or percutaneous coronary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…[2][3][4][5][6][7] Despite this, CR participation remains suboptimal, especially for racial and ethnic minority groups, women and individuals from underserved populations. 1,2,[8][9][10][11][12][13][14][15][16] Barriers to CR participation have been described in prior research and include modifiable patient and systemic factors such as inflexible hours, transportation limitations, travel costs, and lack of insurance coverage for CR costs. 12,13,[17][18][19][20] Studies have shown that patients often prefer CR programs that occur at home or in non-clinical settings with more flexible hours, circumventing many of these barriers.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Despite this, CR participation remains suboptimal, especially for racial and ethnic minority groups, women and individuals from underserved populations. 1,2,[8][9][10][11][12][13][14][15][16] Barriers to CR participation have been described in prior research and include modifiable patient and systemic factors such as inflexible hours, transportation limitations, travel costs, and lack of insurance coverage for CR costs. 12,13,[17][18][19][20] Studies have shown that patients often prefer CR programs that occur at home or in non-clinical settings with more flexible hours, circumventing many of these barriers.…”
mentioning
confidence: 99%
“…4 Seeing the complexity of behavioral change, researchers have sought to identify, and then target, the factors that are more likely to influence CR adherence. 5,6 In this issue of the Journal of Cardiopulmonary Rehabilitation and Prevention, Collins et al 7 offer insights into potential predictors of CR adherence by considering a host of clinical, demographic, and exercise testing variables measured at the start of the influential Heart Failure-A Controlled Trial Investigating Outcomes of Exercise Training (HF-ACTION) randomized controlled trial. In HF-AC-TION, participants were randomized to usual care plus aerobic exercise training composed of 3 mo of supervised facility-based training, followed by home-based exercise, or usual care alone.…”
mentioning
confidence: 99%
“…3 Recently, cardiac rehabilitation (CR) based on exercise training has become an important complementary treatment for cardiac diseases, such as myocardial infarction, coronary artery bypass grafts, and heart failure. [4][5][6][7] A previous study 8 has shown that CR can improve exercise ability and quality of life (QoL) after catheter ablation of AF without increasing the recurrence rate of AF. However, the impact of CR on patients with AF with LAA occlusion remains unknown.…”
mentioning
confidence: 99%